Protein engineering of an industrially-used lipase - Kennedy, Ann (2001)
Lipase 3 is a fungal lipase produced industrially for use as a dough-conditioning enzyme in bread making. Mutants of Lipase 3 were designed to improve enzyme specific activity and to prevent N-linked glycosylation, which was found to cause a drop in activity on industrial-scale production. These were based on three-dimensional model structures of Lipase 3 in `open' and `closed' conformational states derived from crystallographic data of fungal lipases sharing high sequence homology.